Guidance and Counseling In Elementary School or Madrasah Ibtidaiah - Muhamad Nursandi; Siti Meylan Antikadewi (Asesment : Journal Of Counseling Guidance, 2023)
Implementation of guidance and counseling is very necessary in elementary schools, because in practice not a few students who take part in the teaching and learning process face problems that come from themselves and the surrounding environment. Among the problems students often encounter in the field, include playing alone when the teacher is explaining lessons, not wanting to do homework, fighting with friends, getting angry at friends who make mistakes, not attending school, talking dirty and cheating on exams. Schools as educational institutions are responsible for fostering student character, therefore the role of guidance and counseling in elementary schools and madrasah ibtidaiah is very important for the continuity of educational activities in the present and in the future.